Kant's transcendental idealism [an interpretation and defense] - Allison, Henry E. 1937-2023 (Yale University Press, 2004)
This landmark book is now reissued in a new edition that has been vastly rewritten and updated to respond to recent Kantian literature. It includes a new discussion of the Third Analogy, a greatly expanded discussion of Kant's Paralogisms, and entirely new chapters dealing with Kant's theory of reason, his treatment of theology, and the important Appendix to the Dialectic.
Includes bibliographical references and index
Keywords: Kant, Immanuel <1724-1804>; Kant, Immanuel -- 1724-1804; Transcendentaal idealisme; Transzendentalphilosophie; Transzendentaler Idealismus